An integrated approach for trust management based on policy, community adherence and reputation. (30th May 2013) - Valarmathi, J.; Uthariaraj, V. Rhymend
Pervasive computing is a decentralised open environment where different devices interact without prior knowledge of each other, involving a large amount of data. Evaluating the relationship among heterogeneous devices in pervasive computing environment is a challenging task. In a distributed pervasive environment a device might be interested in knowing whether a provider has the information security practices certified by international standard authorities and also has high reputation due to past transactions with other consumer. Therefore an integrated approach (Policies and Recommendations) is proposed in this paper. The concept of community is also introduced for efficient maintenance of devices so that the dynamic topology and mobility issues of ubiquitous devices are handled efficiently. The gossiping (where and when the nodes are idle they exchange or share their history of interactions) technique is highly useful in the proposed model to control false recommendation of malicious spies and to efficiently update trust values frequently.